EFEKTIFITAS PENGGUNAAN SISTEM INFORMASI REKAPITULASI (SIREKAP) DALAM PROSES PELAKSANAAN PEMILU 2024 DI KPU KOTA SURAKARTA - Legistina, Yulla Diyan; Winduro, Wirid (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
Elections are one of the main pillars of democracy that function as a means for the community to legitimately determine leaders and deputy leaders. The voting process in elections has a very crucial role in ensuring fairness, transparency, and legitimacy of election results. One of the latest innovations implemented by the KPU is the use of Sirekap, a digital platform that functions to digitize the vote recapitulation process from polling stations (TPS) in real-time. However, this innovation has several obstacles such as data security issues, accuracy and vote recapitulation, availability of technological infrastructure, and limited digital skills of election officers. This study aims to determine the effectiveness of the use of the recapitulation information system (sirekap) in the 2024 presidential and vice presidential elections and legislative institutions at the KPU of Surakarta City. This study uses the theory of effectiveness according to James L. Gibson, namely productivity, quality, efficiency, flexibility, satisfaction. The approach used is descriptive qualitative with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Data collection was carried out through observation, interviews and documentation. The informant determination technique was purposive sampling. Based on the research conducted, the effectiveness of the use of recapitulation information (sirekap) is considered quite effective, although there are still several obstacles in its implementation. There are several improvements that have emerged in the implementation of this sirekap, such as internet networks, mobile devices, server power, and also in terms of human resource capacity. This is proven based on the results of interviews conducted according to research informants, namely the Head of Section and Head of Sub-Section of the Technical Division of the Surakarta City KPU, PPK Members, PPS Members, and KPPS.